Bilateral carotid-cavernous fistula presented with unilateral symptomatology - Stojčić, Milan; Djurić, Gordana; Žorić, Lepša (Vojnosanitetski pregled, 2020)
Abstract Introduction. Carotid-cavernous fistula presents an abnormal communication between carotid arterial system and the venous cavernous sinus. Due to anatomical characteristics of the sinus, the clinical picture is first manifested as ophthalmic problem. These fistulas are either of spontaneous or traumatic origin with different hemodynamics. They are usually on one side. However, bilateral carotid-cavernous fistulas are rare and deserve special interest. Case report. We presented a 76-years-old female patient, who complained on diplopia and right eye protrusion and esotropia. Ophthalmological findings aroused suspicion of a right-side spontaneous carotid-cavernous fistula. Further non-invasive and invasive investigations confirmed our initial diagnosis. Unexpectedly, digital subtraction angiography revealed another fistula, on her left side. Both fistulas were of low flow and did not need therapy. Conclusion. Carotid-cavernous fistula represent certain diagnostic and therapeutic challenge. Although they are not indicated in a clinical picture, sometimes bilateral fistulas can be found during appropriate diagnostic procedures.